Use of a "Catalytic" Cosolvent, N, N‐Dimethyl Octanamide, Allows the Flow Synthesis of Imatinib with no Solvent Switch. (12th January 2016) - Yang, Jeffrey C.; Niu, Dawen; Karsten, Bram P.; Lima, Fabio; Buchwald, Stephen L.
Abstract: A general, efficient method for C−N cross‐coupling has been developed using N, N ‐dimethyloctanamide as a catalytic cosolvent for biphasic continuous‐flow applications. The described method was used to generate a variety of biarylamines and was integrated into a two‐step sequence which converted phenols into biarylamines via either triflates or tosylates. Additionally, the method was applied to a three‐step synthesis of imatinib, the API of Gleevec, in good yield without the need of solvent switches.